Beyond pharmacological treatment: an insight into therapies that target specific aspects of heart failure pathophysiology. Issue 10175 (9th March 2019) - Normand, Camilla; Kaye, David M; Povsic, Thomas J; Dickstein, Kenneth
Summary: Heart failure is a common syndrome associated with substantial morbidity and mortality. The management of symptoms and the strategies for improving prognosis have largely been based on pharmacological treatments. The pathophysiology of heart failure is complex because of the multiple causes responsible for this syndrome. This Series paper presents some examples of advances in heart failure management, in which the treatment specifically targets the underlying pathophysiological mechanisms responsible for the symptoms. These treatments include treatment of electromechanical dyssynchrony and dysrhythmia by cardiac resynchronisation and implantable cardioverter-defibrillators; neurohumoral modification by baroreflex and vagal stimulation; prevention of adverse cardiac remodelling by interatrial shunts; and finally targeting the myocardium directly by cell therapy in an attempt to regenerate new myocardial cells.